Research Studies in Higher Education: Educating Multicultural College Students - Hamilton, Cory; Leon, Raul A. (Journal of International Students, 2015)
Research Studies in Higher Education: Educating Multicultural College Students is a collection of nine studies that examine the experiences of underrepresented students enrolled in colleges and universities across the US. Presenting both quantitative and qualitative findings, this book enhances our understanding of current topics such as equity, access, achievement, and retention, focusing on the experiences of students. For international students and scholars, this book offers an insight into significant hurdles faced by many multicultural and non-traditional students and recommendations presented to improve college retention and academic success. This book examines the effectiveness of programs and policies intended to assist students of color, first generation college students, low-income students, undecided students, and non-traditional students.